Rancang Bangun Purwarupa Wi-Fi Koin dengan Suplai Daya dari Pembangkit Listrik Tenaga Surya (PLTS) Off-Grid - Widiyatmika, I Made Padma; Aradea, I Gd. Bayu Ananta; Putra, Kadek Arie Anggara; Hartawan, I Gusti Agung Komang Diafari Djuni; Santiari, Dewa Ayu Sri; Pramaita, Nyoman (Innovative: Journal Of Social Science Research, 2025)
Songan Village faces challenges in accessing affordable and stable internet due to its hilly terrain, which hinders telecommunication signals. To address this issue while supporting the renewable energy mix target in accordance with Government Regulation No. 79 of 2014, a prototype of Coin Wi-Fi powered by an off-grid Solar Power Plant (PLTS) was developed as a solution for low-cost and eco-friendly internet access. The system includes bandwidth and usage time management using MikroTik and Raspberry Pi, an off-grid power supply from solar panels and LiFePO4 batteries. Based on observations and testing, the system can operate for 12 hours per day with stable voltage, strong signal up to 20 meters, and consistent internet performance even with multiple users, making it a promising solution for internet access in remote areas.